Effect of Free Convection Flow of a Visco-elastic Fluid Past an Infinite Vertical Flat Plate in Presence of a Transverse Magnetic Field (Chemical Engineering Research Bulletin, 2008)
The unsteady free convection flow of a visco-elastic electrically conducting fluid past an infinite non-conducting vertical plate in presence of transverse magnetic field has been studied. The magnetic lines of force has been fixed relative to the plate. Laplace transform technique has bee employed to solve the basic differential equations. The influence of Grashof number G, elastic parameter S and magnetic field parameter M on the velocity distribution and skin friction have been presented for (1) Impulsive motion and (2) Uniformly accelerated motion of the plate. The velocity profile increases with the increase in time parameter t and Grashof number G for impulsive motion as well as for uniformly accelerated motion. The effect of elastic parameter is to decrease the velocity field for Pr > 1 in case of both the motions. The skin friction is greater in the case of uniformly accelerated motion than in the case of impulsive motion for heating and cooling of the plate for small Ï.Chemical Engineering Research Bulletin 10 (2007) 11-31